Effects of instructional feedback on multiple repertoire acquisition in children with autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Instructional feedback (IF) can increase efficiency in teaching children with autism spectrum disorder (ASD). It can be additional information in the consequent portion of the teaching contingency of a repertoire (primary target). Other abilities (secondary targets) can emerge from this. The aim of this study was to measure the effects of teaching simple tact with IF on the emergence of four other repertoires in four children with ASD. They had no previous experience with FI. The new repertoires emerged fully for one child and partially for another. There was no emergency effect on the other two children. The results were discussed regarding the potential of IF to establish multiple secondary targets without direct teaching, but alternatives are important for children with whom the procedure is not efficient. It was concluded that IF can be an efficient approach for some children with ASD.